Kelayakan Usaha Budidaya Ayam Petelur (Analisis Biaya Manfaat dan BEP Pada UD KR Farm, Cilacap) - Pamungkas, Muhamad Rijal (Jurnal Social Economic of Agriculture, 2020)
In the implementation of a livestock business, the use of production factors such as feed, efficiently becomes a benchmark in determining the profits derived from the business. This study aims (1) to determine the effect of feed prices on egg production (2) to determine the financial feasibility of the business in terms of cost and benefit analysis and how much BEP (Break Event Point) of laying hens. The data used are production data and feed prices for the period January 2019 - December 2019 at the KR Farm farm, Kuripan Kidul, Kesugihan, Cilacap. The data analysis technique uses regression analysis. The results of this study found that there was an effect of the price of feed on egg production, KR Farm said to be feasible where it obtained an R / C value of 2.69, while the value of B / C = 1.69, BEP (price) Rp. 438.49 items, BEP (production) of 454,281.74 items, and ROI of 1,69%. Suggestions that can be put forward in this study include, preferably the KR Farm can maintain its business that has good and decent performance so far, if seen from the price of feed it will further maintain its egg production, can also increase the profits obtained by increasing the number of laying hens in the future so that the increase in turnover obtained is Rp. 1,783,592,221 per month, and reduce the amount of BEP that can be done by increasing the selling price of eggs or by reducing total costs.Keywords: Laying hens, Egg production, Feed prices, Cost and Benefit analysis, Break Even Point analysis